Comment lisait-on une lettre au Moyen Âge ? Le témoignage du Roman du Mont Saint-Michel - Catherine Bougy (Tabularia)
A digression in the Roman du Mont Saint-Michel, a French poem by William of Saint-Pair, monk at Mont Saint-Michel, is a particularly good example of how in the twelfth century one should read out a letter to a high ranking person. The official document in Latin, recognisable as such by its valediction, valei, is a papal letter presented probably in the form of a parchment roll. It is entrusted to a "chaplain" who "unrolls" it, examines it attentively and "recites" to Richard I of Normandy what he "understands" of the text, while translating it for him without "losing" the contents.